Fundamentals of nursing - 4 0 16; Potter, Patricia Ann.;Perry, Anne Griffin; 5 (St. Louis, Missouri : Mosby Elsevier, 2009)
Scope and content: Enhanced Multi-Media CD Fundamentals of Nursing contains NCLEX examination review questions and various added features relating to each chapter of the book, including auto summaries, case studies, video clips, skills performance checklists, and skills updates.
Nursing today -- The health care delivery system -- Community-based nursing practice -- Theoretical foundations of nursing practice -- Evidence-based practice -- Health and wellness -- Caring for the cancer survivor -- Caring in nursing practice -- Culture and ethnicity -- Caring for families -- Developmental theories -- Conception through adolescence -- Young to middle adult -- Older adult -- Critical thinking in nursing practice -- Nursing assessment -- Nursing diagnosis -- Planning nursing care -- Implementing nursing care -- Evaluation -- Managing client care -- Ethics and values -- Legal implications in nursing practice -- Communication -- Client education -- Documentation and informatics -- Self-concept -- Sexuality -- Spiritual health -- The experience of loss, death, and grief -- Stress and coping -- Vital signs -- Health assessment and physical examination -- Infection prevention and control -- Medication administration -- Complementary and alternative therapies -- Client safety -- Hygiene -- Oxygenation -- Fluid, electrolyte, and acid-base balance -- Sleep -- Pain management -- Nutrition -- Urinary elimination -- Bowel elimination -- Mobility and immobility -- Skin integrity and wound care -- Sensory alterations -- Care of surgical clients.;Companion CD-Rom contains: [Section 1] Exercises: NCLEX-syle review questions -- Drag and drop exercises -- Hangman exercises -- Match it exercises -- [Section 2] ]Audio: Audio glossary -- [searchable] English/Spanish audio glossary -- Audio chapter summaries -- Butterfield's Fluids and electrolytes tutorial -- Saxton test-taking skills.
Includes bibliographical references (p. 1409-1439) and index.
Keywords: 2 -- 0; 6; sygepleje. -- 20; 20; 2